THE REFORM OF LEO KESTENBERG – KODÁLY PARALLELS IN THE GERMAN MUSIC EDUCATION OF THE 20th CENTURY - MIKE, Ádám (Studia Universitatis Babes-Bolyai Musica, 2023)
Music education in Hungary has proven to have German roots. German textbooks and terminology were used in Hungary until the first decade of the 20th century, and German was the official language of music education. In this dissertation, we shall attempt to present the work and philosophy of Leo Kestenberg (1882-1962), and hereby an analogy with Kodály principles can appear. The two prominent music pedagogical reformers of the 20th century formulated essentially similar goals on several points. This proves that not only the common roots, but also the reform measures of the 20th century form a strong bond between the music education of the two countries.